Microstructure of AlCrFeSi Alloys Prepared by High-Pressure Spark Plasma Sintering - Knaislová, Anna; Kučera, Daniel; Michalcová, Alena; Marek, Ivo; Cygan, Sławomir; Jaworska, Lucyna (Manufacturing Technology Journal, 2018)
The rapidly solidified aluminium alloy with slowly diffusing transition metals (iron, chromium) prepared by powder metallurgy techniques is characterized by higher thermal stability in comparison with other common aluminium alloys thanks to hardening of dispersed intermetallic phases. The solubility of transition metals in aluminium is increased by rapid solidification, however, their content, in the alloy, is simultaneously significantly reduced due to the formation of hard and brittle intermetallic phases, which lessen plasticity, ductility, and strength of the material. This work is devoted to the description of a microstructure of AlCr6Fe2Si1 alloy prepared by gas atomization followed by consolidation by High-Pressure Spark Plasma Sintering, and comparison of the influence of various sintering conditions on the microstructure of alloy. The low-porosity compacted alloys are formed by quasi-crystalline phase Al95Fe4Cr, the crystalline phase Al13Cr2, and Al80Cr13.5Fe6.5 in the aluminium matrix. They are formed by powder particles with the different internal morphology of intermetallic phases (spherical clusters or snowflakes).
Keywords: Gas atomization; Aluminium alloys; X-ray diffraction; Spark Plasma Sintering; Microstructure